PENERAPAN PRANATA TRUSTS DALAM PENGELOLAAN YAYASAN (SUATU TEROBOSAN EQUITY DALAM HUKUM HARTA KEKAYAAN INDONESIA) - Sardjana Orba Manullang (The Juris, 2019)
Trust in the foundation must show clarity for the beneficiary. At present the foundation is unclear. This ambiguity is caused by the foundation being a social institution, while the benefit is only for individuals who are not public, for example in the trustee. Trustees only use assets if owned by a legal entity, in the principle of beneficiary assets owned by the public. The foundation after the enactment of Law Number 28 of 2004 concerning Amendments to Law Number 16 Year 2001 concerning Foundations does not occur because the trustee cannot own assets that become legal entities. If there is a legal entity, the trustee becomes an absolute owner, it cannot be, the foundation has become ambiguous since the foundation law, the foundation should belong to the beneficiary. Ownership of benefits can be either goods / services or services. But in the management of the foundation, management is carried out on objects (zaak). The application of Trusts institutions in the management of foundation assets in Indonesia prior to the enactment of Law Number 28 of 2004 concerning changes to Law Number 16 of 2001 concerning Foundations by using doctrines in law, then departs from the initial conception of Anglo Saxon legal traditions regarding trust , where the settlor surrenders the right of ownership (dominium) to the trusts in the form of registered owner (legal owner) and beneficiary in the form of equitable owner, it is clear that by surrendering the object in the trust to the trustee, the settlor no longer has any interest any more for objects submitted in trusts (except in resulting trusts). Through the theory formed from the doctrine, it can be stated that the trust is an understanding aimed at an institution tasked with managing property that is not his property and is intended for the benefit of other parties outside the party who gave away the property and trustee.